La alimentación en el desarrollo de los aprendizajes significativos de los niños y las niñas que asisten al programa de desarrollo comunitario “Caminemos Juntos” del barrio Víctor Emilio Valdivieso, parroquia Sucre, cantón y provincia de Loja, año lectivo 2012-2013. Lineamientos propositivos - González Cajilima, Elizabeth Cristina (2014)
To develop the research work called, THE FOOD IN THE DEVELOPMENT OF SIGNIFICANT LEARNING OF CHILDREN ATTENDING THE COMMUNITY DEVELOPMENT PROGRAMME "WALK TOGETHER" THE DISTRICT VICTOR EMILIO Valdivieso, PARISH SUCRE, CANTON AND Loja Province SCHOOL YEAR 2012 -. propositional GUIDELINES 2013, with the overall aim of revealing the importance of food in developing meaningful learning of the children who attend the community development program, it was necessary to use the scientific method, the analytical method - synthetic, as well as the appropriate quantitative and qualitative analysis of the results and the deductive method, thus facilitating the study of the issues raised about the consequences resulting from poor eating habits in the family mainly in children . The research population consists of 126 people, 63 children attending the community development program and 63 representatives Walk Together fathers or mothers, for it were applied techniques, direct observation; and the survey that was applied to it. Then the results of the field research is presented, to arrive at the testing of hypotheses, conclusions, recommendations and proactive guidelines; obtaining as most relevant result, most children do not eat properly, however, it get meaningful learning because motivation and demand their parents or represented. It is for this reason that the parents who are aware of the importance of properly feed their children is recommended, as this will participate in the development and greatly facilitate the learning of their children.